2011
DOI: 10.1111/j.1600-079x.2011.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of melatonin in progesterone production by human luteal cells

Abstract: This study investigated whether melatonin protects luteinized granulosa cells from reactive oxygen species (ROS) as an antioxidant to enhance progesterone production in the follicle during ovulation. Follicular fluid was sampled at the time of oocyte retrieval in women undergoing in vitro fertilization and embryo transfer (IVF-ET). Melatonin concentrations in the follicular fluid were positively correlated with progesterone concentrations (r = 0.342, P < 0.05) and negatively correlated with the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 46 publications
5
66
0
1
Order By: Relevance
“…However, the presence of high melatonin levels in follicular fluid (Brzezinski et al 1987) and the presence of receptors in granulosa cells (Yie et al 1995, Niles et al 1999, Woo et al 2001, Soares et al 2003a, Wang et al 2012, Barros et al 2013 have suggested a role of melatonin on ovarian function. This hypothesis has been confirmed by recent studies reporting strong evidence for melatonin action on the ovary, such as modulation of ovarian steroidogenesis (mainly progesterone (P 4 ) production; Taketani et al 2011) and contribution in the maintenance of a proper follicular structure and function (Soares et al 2003a,b, Barros et al 2013, Maganhin et al 2013. In a previous study, we demonstrated that melatonin supplementation during the anoestrous period modifies the pattern of follicular waves by increasing the turnover of dominant follicles (Berlinguer et al 2009).…”
Section: Introductionsupporting
confidence: 62%
“…However, the presence of high melatonin levels in follicular fluid (Brzezinski et al 1987) and the presence of receptors in granulosa cells (Yie et al 1995, Niles et al 1999, Woo et al 2001, Soares et al 2003a, Wang et al 2012, Barros et al 2013 have suggested a role of melatonin on ovarian function. This hypothesis has been confirmed by recent studies reporting strong evidence for melatonin action on the ovary, such as modulation of ovarian steroidogenesis (mainly progesterone (P 4 ) production; Taketani et al 2011) and contribution in the maintenance of a proper follicular structure and function (Soares et al 2003a,b, Barros et al 2013, Maganhin et al 2013. In a previous study, we demonstrated that melatonin supplementation during the anoestrous period modifies the pattern of follicular waves by increasing the turnover of dominant follicles (Berlinguer et al 2009).…”
Section: Introductionsupporting
confidence: 62%
“…The ovulatory process is similar to a local inflammatory response, resulting in high levels of reactive species [83] among which ROS may potentially damage granulosa cells undergoing luteinization during ovulation [89]. As in folliculogenesis, melatonin has a variety of functions at different luteal stages.…”
Section: In the Corpus Luteummentioning
confidence: 99%
“…The sensitivity of 8-OHdG was 0.5 ng/ml, and the CV for intra-and inter-assay were 5.5% and 6.1%, respectively. HEL concentrations were measured using an ELISA kit (Japan Institute for the Control of Aging) as we reported previously [26,27]. Each sample of follicular fluid (50 μl) was pretreated with chymotrypsin to perform proteolysis, and filtered using an ultrafilter (cut off molecular weight 10 kDa) for duplicate assay.…”
Section: Measurement Of Tnfα Il-6 Oxidative Stress Markers and Antmentioning
confidence: 99%